Prediction of right ventricular dysfunction from radiographic estimates of right descending pulmonary artery in hemodynamically stable pulmonary embolism patients - (:unkn) unknown (VIA MEDICA, 2013)
Background: The evaluation of right ventricular (RV) dysfunction by echocardiography is one of the most important established determinants of the prognosis of acute pulmonary embolism. The aim of the study was to investigate possible association between diameter of right descending pulmonary artery on chest X-rays and RV dysfunction by echocardiography in hemodynamically stable pulmonary embolism patients. Methods: Eighty-nine patients with the diagnosis of hemodynamically stable pulmonary embolism were included. Results: The frequency of RV dysfunction was significantly higher in patients with an enlarged right descending pulmonary artery on chest X-rays (p = 0.001). There was a significant positive correlation between the diameter of the right descending pulmonary artery on postero-anterior chest X-rays and the diameter of the RV (r = 0.469; p = 0.002). Diameter of right descending pulmonary artery on chest X-rays was also found as a significant predictor of RV dysfunction besides the troponin-T levels and systolic pulmonary arterial pressure (p < 0.05). Conclusions: Diameter of right descending pulmonary artery on chest X-rays may provide information about the risk for pulmonary embolism patients and may be used as a prognostic radiological parameter for the appropriate management of acute pulmonary embolism. (Cardiol J 2013; 20, 2: 184-189)
Keywords: pulmonary embolism; right ventricular dysfunction; BRAIN NATRIURETIC PEPTIDE; RISK STRATIFICATION; PROGNOSTIC ROLE; ECHOCARDIOGRAPHY; HYPERTENSION; TROPONIN; DIAGNOSIS; PERFUSION; PRESSURE; REGISTRY